A Buffer-Sizing Algorithm for Network-on-Chips with Multiple Voltage-Frequency Islands. (28th February 2012) - Kumar, Anish S.; Kumar, M. Pawan; Murali, Srinivasan; Kamakoti, V.; Benini, Luca; De Micheli, Giovanni
Abstract : Buffers in on-chip networks constitute a significant proportion of the power consumption and area of the interconnect, and hence reducing them is an important problem. Application-specific designs have nonuniform network utilization, thereby requiring a buffer-sizing approach that tackles the nonuniformity. Also, congestion effects that occur during network operation need to be captured when sizing the buffers. Many NoCs are designed to operate in multiple voltage/frequency islands, with interisland communication taking place through frequency converters. To this end, we propose a two-phase algorithm to size the switch buffers in network-on-chips (NoCs) considering support for multiple-frequency islands. Our algorithm considers both the static and dynamic effects when sizing buffers. We analyze the impact of placing frequency converters (FCs) on a link, as well as pack and send units that effectively utilize network bandwidth. Experiments on many realistic system-on-Chip (SoC) benchmark show that our algorithm results in 42% reduction in amount of buffering when compared to a standard buffering approach.